2021
DOI: 10.1186/s13287-020-02123-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic proteomic profiling of human periodontal ligament stem cells during osteogenic differentiation

Abstract: Background Human periodontal ligament stem cells (hPDLSCs) are ideal seed cells for periodontal regeneration. A greater understanding of the dynamic protein profiles during osteogenic differentiation contributed to the improvement of periodontal regeneration tissue engineering. Methods Tandem Mass Tag quantitative proteomics was utilized to reveal the temporal protein expression pattern during osteogenic differentiation of hPDLSCs on days 0, 3, 7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 90 publications
3
20
0
Order By: Relevance
“…PDLSCs exhibit osteoblast-like characteristics and are able to differentiate into osteoblasts or osteoblasts. They are also considered as the optimal seed cells for periodontal regeneration [ 49 ].…”
Section: Pdlsc Sheets Applicationsmentioning
confidence: 99%
“…PDLSCs exhibit osteoblast-like characteristics and are able to differentiate into osteoblasts or osteoblasts. They are also considered as the optimal seed cells for periodontal regeneration [ 49 ].…”
Section: Pdlsc Sheets Applicationsmentioning
confidence: 99%
“…For example, several studies have reported controversial results for the effects of HG on the differentiation of PDL cells (45)(46)(47). The overexpression of LIN28A enhances the osteogenic process and calcified nodule formation by increasing lactate and ATP production and decreasing reactive oxygen species production (30); furthermore, proteomic analysis of human PDL cells has identified OXPHOS as the most significantly upregulated pathway during their osteogenic differentiation (48). Elucidation of the dynamic metabolic preference of PDL cells during differentiation will presumably explain the discrepancy among several studies on the energy metabolism of PDL cells.…”
Section: Understanding Energy Metabolism In Pdl Cells: a Possible Strategy For Periodontal Regenerationmentioning
confidence: 99%
“…These differences in salivary protein profiles can be used as disease indicators and help in the diagnosis [ 124 ]. Proteomic profiling of gingival crevicular fluid for disease biomarkers and osteogenic differentiation potential in periodontal ligament stem cells has provided new avenues for diagnosis and periodontal regeneration [ 125 , 126 ]. Evaluations and comparisons of the proteome profile could highlight alterations in diseased and healthy conditions and drive the discovery of prospective biomarkers.…”
Section: Proteomicsmentioning
confidence: 99%